A study on biological activities of Bouea macrophylla Griff leaf extract - Hai Ha, Pham Thi; Kien Cuong, Tran; Thu Nha, Nguyen Thi; Hoang Lan, Nguyen Phan; Thuan Anh, Nguyen Huu; Long Giang, Bach; Minh Quan, Pham; Quoc Toan, Tran; Quoc Long, Pham; Thanh Luan, Nguyen (Vietnam Journal of Biotechnology, 2022)
Bouea macrophylla in the family Anacardiaceae is a prominent fruit in Southeast Asia, especially in Vietnam with several prospects. This study focused on the bioactive components and biological effects of B. macrophylla ethanol leaf extract. Phytochemical analysis revealed various compounds including polyphenol, tannin, saponin, reducing agent, flavonoid, and essential oil in the extract. The DPPH assay showed the remarkable antioxidant capacity of the extract (IC50 = 6.4 ± 0.08 μg/ml), which is stronger than ascorbic acid (IC50 = 9.35 ± 0.12 μg/ml). The disc diffusion method and minimal inhibitory concentration test displayed the significant antibacterial ability of the extract against Listeria monocytogenes, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhimurium, and Bacillus cereus at the range from 10 - 15 mg/ml, but no activity against Staphylococcus aureus. Moreover, the MTT assay was performed the noticeable anticancer activity of the extract in HepG2 (IC50 = 72.33 ± 0.68 μg/ml), and MCF-7 cells (IC50 = 50.25 ± 1.36 μg/ml). Taken together, this study indicated the effects of B. macrophylla ethanol leaf extract from Vinh Long Province, Vietnam on antibacterial, antioxidant, and anticancer properties. Therefore, B. macrophylla possibly is used in the food industry and medicine.